Ventricularpre-excitationand Ebstein anomaly in a patient with Phelan Mc Dermid syndrome: A case report - Flavia Caime; Aurora Framcesca Meo; Francesco De Luca; Letteria Bruno; Maria Pia Calabrò; Eloisa Gitto (Atti della Accademia Peloritana dei Pericolanti - Classe di Scienze Medico-Biologiche, 2022)
Phelan-McDermid syndrome (PMS) or deletion 22q13 syndrome is a rare genetic syndrome resulting from loss of 22q13 region involving the SHANK3 gene. Main features are neonatal hypotonia, global developmental delay, absent to severely delayed speech and minor dysmorphic features. The true incidence remains unknown. The deletion can be detected by high resolution chromosome analysis, confirmed by fluorescence in situ hybridization (FISH) or array comparative genomic hybridization (aCGH). Ebstein’s anomaly (EA) is a rare congenital heart disease (1:20.000 live births) that consists in tricuspid valve’s malformation: from minimal displacement of the septal and posterior leaflets to involvement of right ventricular outflow with functional pulmonary atresia and severe right ventricular dysfunction. This condition leads to a large spectrum of clinical presentations. EA patients have a large incidence of tachyarrhythmias, most of which can be attributed to accessory atrioventricular pathways that could be observed to electrocardiogram as ventricular pre-excitation. We describe a case of a child with PMS and accidental finding of ventricular pre-excitation to electrocardiogram that underlined the presence of EA.